Parametrization of a non-local turbulent exchange - Voloshchuk, V.M.; Voloshchuk, Ja.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The general analysis of the methods of parametrization of the turbulent diffusion of a gas-aerosol impurity used in applied researches is carried out. With this purpose, the original way of representation of the equations of conservation of a matter in the operator form is used. The schemes, circuits of non-local parametrization of the turbulent exchange, which generalize their known gradient forms, are obtained and physically proved, probably for the first time.